PENYELESAIAN HUKUM TERHADAP BENTUK DISKRIMINASI DAFTAR PEMILIH TAMBAHAN DALAM PEMILUKADA - Arba’in, Arba’in; Marwiyah, Siti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study aims to identify and analyze various forms of discrimination against supplementary voter lists in the context of general elections. The main focus of this research is to uncover the dynamics of discrimination that may be experienced by voters listed in the supplementary voter lists, whether systematically or sporadically. Additionally, this study seeks to explore effective and applicable legal mechanisms to address this discrimination. By analyzing the existing legal framework and relevant case studies, this research is expected to offer comprehensive and practical solutions Furthermore, this study strives to make a significant contribution to the formulation of fairer and more inclusive election policies. Through policy recommendations based on empirical findings, it is hoped that the electoral system can be improved to ensure more effective protection of supplementary voters’ rights. Additionally, this research aims to strengthen the legal protection framework for supplementary voters, ensuring that every individual has an equal opportunity to participate in the democratic process. The results of this study are expected to serve as a reference for policymakers and legal practitioners in efforts to enhance the quality and integrity of the electoral system